An Empirical Analysis of Factors Influencing Reward and Recognition Systems Followed in Selected Garments Industries in Tirupur - Rajeswari.R; Balamurugan, D (Management Journal for Advanced Research, 2022)
Even though people work for salary or wages (rewards), there are numerous ways of rewarding (motivating) employees according to the task or function performed. The underlying principle for the use of rewards is to motivate or induce behaviours among employees which are viewed as beneficial for enhanced performance whilst inhibiting other behaviours which employers and managers perceive as detrimental to organizational effectiveness and efficiency. Thus, rewards serve as a means of motivating desired behaviors. Incentives, rewards and recognitions are the prime factors that impact on employee motivation. Many researchers opined that, employees who are well motivated serve as the competitive advantage for any company because their performance leads an organization to accomplishment of its goals. Among financial, economic and human resources. human resources are the most vital that can provide a company’s competitive edge as compared to others. The main aim of the study is to examine the impact of reward and recognition on job satisfaction and motivation. The present study assess the Factors influencing reward and recognition systems followed in selected garments industries in Tirupur.